Clinical and Molecular Characterization of NF1 Patients: Single-Center Experience of 32 Patients From China. Issue 10 (March 2016) - Zhu, Lude; Zhang, Yunfeng; Tong, Hanxing; Shao, Minhua; Gu, Yong; Du, Xufeng; Wang, Peiru; Shi, Lei; Zhang, Linglin; Bi, Mingye; Wang, Xiuli; Zhang, Guolong
Abstract : Abstract: Neurofibromatosis type 1 (NF1) is a hereditary disorder caused by mutations in the NF1 gene. Detecting mutation in NF1 is hindered by the gene's large size, the lack of mutation hotspots, and the presence of pseudogenes. Our goal was to establish a sensitive, feasible, and comparatively economical protocol to detect NF1 mutations using blood samples. We developed a method to screen patients for mutations. Thirty-two NF1 patients from 32 unrelated families and 120 unrelated population-match controls were investigated in this study. Specific primers were designed for NF1 to avoid pseudogenes. NF1 mutations were detected by sequencing at the deoxyribonucleic acid (DNA) and complementary DNA (cDNA) levels, and multiplex ligation-dependent probe amplification (MLPA) and familial segregation analyses were used. Forty-four specific primers designed according to the NF1 structure were successfully used for polymerase chain reaction (PCR) and DNA sequencing, which was more feasible and useful than cDNA sequencing. Thirty distinct NF1 mutations were identified in 32 patients. Thirteen mutations were novel and most were frameshift mutations (33.3%). Mutations were detected at a rate of 93.8%. Our study suggests that this sensitive, feasible, and comparatively economical protocol is effective for the detection of NF1 mutations.